Large-scale synthesis of nanopowders by transferred arc thermal plasma. (18th August 2010) - Raut, Varsha B.; Seth, Tanay; Pawar, Amol U.; Shinde, Manish D.; , Dinesh P. Amalnerkar
The present work describes the preliminary results on large-scale synthesis and characterisation of copper (Cu) and aluminium nitride (AlN) nano powders by transferred arc thermal plasma technique. The transferred arc was used to vaporise the precursor materials (Cu, Al metal 99.9% pure). Nano particles are formed in the gas phase as a result of homogeneous nucleation. The vapours of Al were allowed to react with NH3 gas for the synthesis of AlN. Rapid quenching using Ar/N2 then produced the desired nano powders. For the generation of Cu nano powders, argon was used as a quench gas. The resultant nano-powders of Cu, AlN were collected under the controlled atmosphere. TEM and AFM results show the particle size ranging between 70 nm and 100 nm. These particles possess exotic applications in defence systems, armour for aircraft and vehicles, aeronautical systems, power electronics, microelectronics etc.